Health professionals’ willingness to share responsibility and strengthen interprofessional collaboration: a cross-sectional survey - Sophie Karoline Brandt; Stefan Essig; Andreas Balthasar (BMC Medical Education)
Abstract Background Doctors’ unwillingness to share responsibility acts as a major barrier to interprofessional collaboration (IPC). Educating both doctors and allied health professionals in taking on or relinquishing responsibility could enhance IPC. Yet there is no evidence that these educational efforts increase IPC willingness. This study aims to (1) compare the willingness to take on or relinquish responsibility for decision-making in patient care and their willingness to strengthen IPC between members of five main health professions, and (2) investigate associations between the willingness to take on or relinquish responsibility and the willingness to strengthen IPC. Methods We conducted a cross-sectional survey targeting pharmacists, doctors, medical practice assistants, nurses, and physiotherapists in Switzerland. Group differences were assessed, and associations were examined using multivariable logistic regression analyses. Results Overall, 3670 health professionals participated. Members of all allied health professions were highly willing to take on more responsibility for decision-making for patient care (ranging from 74.3% to 86.5%). Medical practice assistants (52.3%) and nurses (46.8%) were highly willing to relinquish responsibility, less so pharmacists (34.2%) and physiotherapists (37.8%); doctors were torn between high (49.2%) and neither high nor low willingness (38%). Members of all professions were highly willing to strengthen IPC (ranging from 76.4 to 91.2%). We found a strong, statistically significant relationship between willingness to take on more responsibility and willingness to strengthen IPC (OR = 5.30, p < .001). The relationship between willingness to relinquish responsibility and willingness to strengthen IPC was smaller (OR = 3.30, p < .001). Conclusion Increasing the health professionals’ willingness to take on responsibility is crucial to strengthen IPC. Increasing the willingness to relinquish responsibility would likely be less effective. Actions required include educational and political efforts to transfer responsibility to allied health professionals and to enable health professionals to decide when it is appropriate to take on or relinquish responsibility. Given the willingness of many health professionals to strengthen IPC, substantial potential in practice is evident.